2004
DOI: 10.1104/pp.103.036970
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Localization of an Abscisic Acid Biosynthetic Enzyme, AAO3, in Arabidopsis

Abstract: Arabidopsis aldehyde oxidase 3 (AAO3) is an enzyme involved in abscisic acid (ABA) biosynthesis in response to drought stress. Since the enzyme catalyzes the last step of the pathway, ABA production sites may be determined by the presence of AAO3. Here, AAO3 localization was investigated using AAO3 promoter:AAO3-GFP transgenic plants and by an immunohistochemical technique. AAO3-GFP protein exhibited an activity to produce ABA from abscisic aldehyde, and the transgene restored the wilty phenotype of the aao3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
140
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(156 citation statements)
references
References 51 publications
9
140
0
4
Order By: Relevance
“…It has been suggested that ABA synthesized in vascular tissues is transported to guard cells (16,17). Therefore, we investigated whether AITs are involved in this process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that ABA synthesized in vascular tissues is transported to guard cells (16,17). Therefore, we investigated whether AITs are involved in this process.…”
Section: Resultsmentioning
confidence: 99%
“…5F). The expression pattern of AIT1 in vascular tissues resembles the localization of ABA biosynthetic enzymes such as AAO3, ABA2, and NCED3 (16,17). Accordingly, we propose a model in which AIT1 functions to maintain the ABA pool size at the site of biosynthesis (vascular parenchyma cells), and this might be required for efficient translocation of ABA to guard cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABA in the form of its inactive glucose ester conjugate is highly mobile throughout the plant and is released into its active form when it has reached the target tissue. Localization studies of ABA biosynthetic enzymes indicate that the vascular bundles are the active sites of ABA synthesis in turgid, non-stressed plants [58,59]. Therefore, all vascular plant tissues have the capacity to synthesize ABA.…”
Section: How Do Plants Resist Pathogens?mentioning
confidence: 99%
“…That this occurs in both vte2 and vte1 strongly suggests that tocopherols play a crucial, previously unrecognized role in low-temperature adaptation, specifically in phloem loading. Several studies have suggested that vascular tissues, including vascular parenchyma, are metabolically distinct, sensitive to changing environmental conditions, and hence critical sites for stress responses (Orozco-Cardenas et al, 2001;Hibberd and Quick, 2002;Fryer et al, 2003;Koiwai et al, 2004;Narvaez-Vasquez and Ryan, 2004). Our data are consistent with this thesis and suggest that tocopherols have important function(s) in regulating the responses of these specific cell types to environmental stress, such as low temperatures.…”
Section: Tocopherol Functions In Plant Stress Physiologymentioning
confidence: 99%